Inhibition of the PI3K/AKT Pathway Sensitizes Oral Squamous Cell Carcinoma Cells to Anthracycline‐Based Chemotherapy In Vitro. Issue 9 (16th May 2017) - Smolensky, Dmitriy; Rathore, Kusum; Bourn, Jennifer; Cekanova, Maria
ABSTRACT: Anthracycline‐based chemotherapy, such as doxorubicin (Dox), while effective against many solid tumors, is not widely used for head and neck cancers. In this study, we evaluated the efficacy of Dox, and its derivative AD198 in human, canine, and feline oral squamous cell carcinomas cells (OSCC) in vitro. Dox and AD198 had significant an anti‐proliferative effect on human, canine, and feline OSCC cells in dose‐dependent manner. AD198 inhibited cell proliferation more effectively than Dox in tested OSCC cells. In the human oral squamous cell carcinoma SCC25 cells, Dox and AD198 increased the production of reactive oxygen species and subsequently increased apoptosis through activation of caspase signaling pathway. Dox and AD198 increased activation of AKT, ERK1/2, and p38 MAPK signaling pathways in tested OSCC cells by dose‐dependent manner. The efficacy of Dox and AD198 treatments in inhibition of cell proliferation was increased in tested OSCC when combined with PI3K/AKT inhibitor, LY294002 treatment. Inhibition of PI3K/AKT reduced Dox‐ and AD198‐induced activation of ERK1/2 and further increased Dox‐ and AD198‐induced phosphorylation of p38 MAPK in OSCC. Our results suggest that the anthracycline therapies, such as Dox or AD198, can be more effective for treatment of OSCC when combined with inhibitors of the PI3K/AKT pathway. J. Cell. Biochem. 118: 2615–2624, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The inhibition of PI3K/AKT reduced Dox‐ and AD198‐induced activation of ERK1/2 and further increased Dox‐ and AD198‐induced phosphorylation of p38 MAPK in OSCC. Our results suggest that the anthracycline therapies, such as Dox or AD198, can be more effective for treatment of OSCC when combined with inhibitors of the PI3K/AKT pathway.